Peran Caregiver dalam Pemenuhan Kepatuhan Minum Obat pada Pasien dengan Halusinasi - Syifa Kamila Habibah; Halimatus Zahro; Muhamad Naufal; Slametiningsih Slametiningsih (Jurnal Ilmu Kesehatan dan Gizi, 2026)
Schizophrenia is a severe mental disorder often accompanied by auditory hallucinations and has a significant impact on patients’ psychosocial functioning. This condition can reduce medication adherence, thereby increasing the risk of relapse. In this context, the role of caregivers is crucial in supporting treatment success. This study aims to describe psychiatric nursing care for patients with auditory hallucinations in improving medication adherence through caregiver involvement. The method used is a case study with a nursing process approach, including assessment, nursing diagnosis, planning, implementation, and evaluation. Interventions focus on hallucination management, psychoeducation, and caregiver involvement in care. The results show an increase in patients’ and families’ knowledge regarding the illness and its treatment, improved medication adherence, and enhanced patient ability to control responses to auditory hallucinations. Caregiver involvement has been shown to assist in supervision and providing support to patients. Therefore, comprehensive psychiatric nursing care through hallucination management, psychoeducation, and caregiver involvement is effective in improving medication adherence and controlling symptoms in patients with auditory hallucinations.